Faktor-Faktor yang Mempengaruhi Penyerapan Tenaga Kerja di Provinsi Kalimantan Selatan - Mursidah; Fahraty, Eny (PPJP ULM, 2019)
This study was conducted to (1) Find out the simultaneous economic growth,provincial minimum wages, and population growth in South Kalimantan Provinceemployment.The study was conducted in the south Kalimantan Province. Data is processedby testing multiple linear regression analysis using SPSS 22.Based on the analysis, the study results prove simultaneously that there is anegative influence of population growth and a positive relationship between economicgrowth and provincial minimum wages on employment in the province of SouthKalimantan partially that the provincial minimum wage in the previous year had avery significant influence on employment in the South Kalimantan Province.